1992
DOI: 10.1016/0014-5793(92)80802-n
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates in mammalian tryptophanyl‐tRNA synthetase

Abstract: Homogeneous preparations of bovine tryptophanyl‐tRNA synthetase (EC 6.1.1.2) contain monosaccharides (mannose, fucose, galactose, N‐acetylglucosamine) as revealed by liquid chromatography. Their content comprises 2.5–3.0% (w/w) of the enzyme composed of two subunits (60 kDa × 2). The same set of sugars was detected in clastase and CNBr‐generated fragments (with molecular masses of approx. 40 kDa and 30 kDa, respectively). It is concluded that bovine tryptophanyl‐tRNA synthetase, in addition to being a metallo‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This phenomenon was confirmed in vivo by using human interferon-y-treated human ovarian cancer xenografts grown in nude mice [12]. Moreover, we have demonstrated that Trp-tRNA synthetase is a human autoantigen in some donors and cancer patients and this was hypothesized to be at least partially related to interferon induction Bovine pancreas Trp-tRNA synthetase is a glycoprotein [14] consisting of two subunits of about 60 kDa each [2]. Our previous studies have shown that it reaches high levels in bovine pancreas and comprises aproximately 3 % of the soluble protein fraction [15].…”
mentioning
confidence: 73%
“…This phenomenon was confirmed in vivo by using human interferon-y-treated human ovarian cancer xenografts grown in nude mice [12]. Moreover, we have demonstrated that Trp-tRNA synthetase is a human autoantigen in some donors and cancer patients and this was hypothesized to be at least partially related to interferon induction Bovine pancreas Trp-tRNA synthetase is a glycoprotein [14] consisting of two subunits of about 60 kDa each [2]. Our previous studies have shown that it reaches high levels in bovine pancreas and comprises aproximately 3 % of the soluble protein fraction [15].…”
mentioning
confidence: 73%
“…The properties of placental hTrpRS and pancreatic bTrpRS seem to be very similar and possibly identical in terms of their putative subunit composition and kinetic parameters ; the size of the placental hTrpRS estimated by SDS/ PAGE is 58 kDa and the isoelectric point is 5.2 [43]. Highly purified bTrpRS is available [24,25,37,391, and recently hTrpRS (y2 protein) was purified (J. J. et al, unpublished data).…”
Section: Comparison Of Mammalian Trprs and Rf And Their Activitiesmentioning
confidence: 96%
“…bTrpRS was purified according to Kisselev et al [24] as modified by Kovaleva et al [25], and was kindly provided by G. Kovaleva. hTrpRS (y2 protein) was purified from interferon-y-induced human amnion cell cultures using chromatography on DEAE-cellulose and heparin-Sepharose columns [17] (and J. J., unpublished results).…”
Section: Trprs Purification and Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…WRS purification and assay Bovine WRS was purified according to Kisselev et al (1979) as modified by Kovaleva et al (1992), and was kindly provided by G.Kovaleva. The WRS activity was measured by tryptophanylation of yeast tRNA enriched in tRNATrp (kindly provided by G.Keith) according to Kisselev et al (1979).…”
Section: Release Assaymentioning
confidence: 99%